Is sport for development already an anachronism in the age of austerity or can it be a space of hope?. Issue 1 (2nd January 2018) - Rossi, Tony; Jeanes, Ruth
ABSTRACT: This paper examines the capacity of sport for development (SfD) to survive within the context of economic austerity. The Global Financial Crisis placed severe pressure on development aid budgets around the world. The effect of this is being felt within low-to-middle income countries (LMIC) and amongst organisations working in the development space. SfD, as a less established development entity, has the potential to struggle for funding in an increasingly competitive development market. This paper considers the current economic situation and examines the potential of a coalescence between the ideas of Sen, Nussbaum and Friere related to development as freedom, a capabilities framework and critical pedagogy as a conceptual framework for reimagining SfD in an era of austerity. We propose that a capability approach, combined with tenets of critical pedagogy, provides a framework which positions SfD as a locally driven, sustainable endeavour that is less reliant on the fortunes of the global economy, where development and progress can be captured and understood at the level of local achievement (capabilities) rather than a reliance on economic metrics.